2014
DOI: 10.1002/j.2161-1882.2014.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation of Master's‐Level Professional Counselors for Positions in College and University Counseling Centers

Abstract: This study investigated college and university counseling center directors' perceptions of the adequacy of the preparation of master's-level counselors for work in college and university counseling centers. Results indicated that counselors were rated on average as prepared; however, many directors had concerns about counselors' ability to work with students presenting more severe mental health issues. Findings are discussed, and implications for the training and preparation of college counseling practitioners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Some counseling literature suggests a greater need for depth in counselor preparation. For example, Shaw, Remley, and Ward (2014) found that while employers perceived novice master’s‐level clinical mental health counselors to be adequately prepared for their job, they also suggested more in‐depth preparation regarding significant mental health issues. Similarly, scholars suggested providing greater depth when preparing counseling students for a range of topics, such as crisis counseling (Barrio Minton & Pease‐Carter, 2011), professional ethics (Urofsky & Sowa, 2004), and mindfulness (Stauffer & Pehrsson, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Some counseling literature suggests a greater need for depth in counselor preparation. For example, Shaw, Remley, and Ward (2014) found that while employers perceived novice master’s‐level clinical mental health counselors to be adequately prepared for their job, they also suggested more in‐depth preparation regarding significant mental health issues. Similarly, scholars suggested providing greater depth when preparing counseling students for a range of topics, such as crisis counseling (Barrio Minton & Pease‐Carter, 2011), professional ethics (Urofsky & Sowa, 2004), and mindfulness (Stauffer & Pehrsson, 2012).…”
Section: Discussionmentioning
confidence: 99%